Change of Beliefs in Pagan Baltics. Curonians - Žulkus, Vladas (Sociologija. Mintis ir veiksmas, 2001)
The aim of the article is to analyze the changes of beliefs in Courland. The author takes his departure in a view that the that the changes of burial customs are related with the change in ideology and develops his analysis by overviewing the history of burial by burning in the region. The author argues that the spread of the custom of burial by burning is an expression of change of beliefs that is connected with the social transformations the society underwent. The author argues that the carrier-groups of change of customs are those of the higher strata. The change of beliefs is discussed by looking into the history of the formation and the growing influence of a fellowship in the higher strata in the V-XI centuries.
Keywords: belief; curonians; burial customs